Factors Affecting the Adoption of one Unified Electronic system that includes all Government services in Saudi Arabia: العوامل المؤثرة في تبني نظام إلكتروني شامل وموحد لجميع الخدمات الحكومية في المملكة العربية السعودية - Yousef Saud Al-Sharari, Ali Mohammed Saghir,Nayef Mohammed Jabali, Abdullah Eid Balawi, Talal Ali Abu Zenda, Ahmed Mohammed Al-Shahrani (Journal of engineering sciences and information technology, 2019)
E-government systems have contributed considerably in increasing the productivity in many different workplace environments. Previous research studies such as (Ashour, 2010, Wafi Al-Balawi, 2014, Hamidallah, Abdel Aziz, Hamdan, 2013) indicated that there is still a need for more research studies about e-Government systems. According to the literature review, there appears to be no study conducted in Saudi Arabia that investigate individuals’ behavioral intention to use a specific e-Government system as a one-stop destination for all electronic services that provided by the Saudi government. Therefore, this study investigated how the perceived ease of use and perceived usefulness of Abshir system can predict Saudi citizens’ behavioral intention to use it as a one-stop destination for all electronic services that provided by the Saudi government. This study sought to answer the following questions: 1) To what extent do the following variables (perceived ease of use and perceived usefulness) predict the behavioral intention to use the Abshir system as a one-stop destination for all electronic services that provided by the Saudi government? And 2) What are Saudi citizens’ views toward the use of the Abshir system as a one-stop destination for all electronic services that provided by the Saudi government? The results of this study showed that the application of e-government appears to be an effective tool for increasing work productivity. It was also found that the use of Abshir system as a one-stop destination for all electronic services can be predicted through its perceived usefulness and perceived ease of use. More of the results and discussion are discussed in this research. Recommendations and suggestions are also discussed and explained for decision-makers and there are worth considering.